Microporous layer, gas diffusion layer and preparation method thereof, membrane electrode and fuel cell
By introducing cerium complexes and cyclodextrin or crown ether compounds into the gas diffusion layer of the fuel cell, the problem of insufficient hydrophobicity of the gas diffusion layer is solved, and the durability of the membrane electrode and the electrochemical performance of the fuel cell are improved.
Patent Information
- Application Number
- CN202411498202.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-03-11
AI Technical Summary
In existing fuel cells, the hydrophobicity of the gas diffusion layer is insufficient, resulting in liquid water accumulation, increasing the risk of electrode flooding and affecting electrochemical performance.
The microporous layer formed by using cerium complex as a radical quencher and combining cyclodextrin or crown ether compounds as ligands has good dispersion and radical quenching ability, improving the hydrophobicity and mass transfer properties of the gas diffusion layer.
The chemical stability and durability of the membrane electrode are improved, the free radical quenching capacity of the gas diffusion layer is enhanced, and the electrochemical performance of the fuel cell is improved.
Smart Images

Figure CN119601698A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and specifically relates to a microporous layer and a gas diffusion layer and a preparation method thereof. Furthermore, the present invention also relates to a membrane electrode and a fuel cell comprising the gas diffusion layer. Background Art
[0002] As the application end of hydrogen energy, proton exchange membrane fuel cells are an emerging technology in the field of clean energy. Currently, all automotive proton exchange membrane fuel cells that are used on a large scale are low-temperature fuel cells, and the membrane electrode needs to achieve ideal working conditions under certain temperature and humidity. The membrane electrode is composed of a proton exchange membrane, a catalyst layer, and a gas diffusion layer, and is the core component that determines the performance of the fuel cell. In the membrane electrode, the chemical degradation of the proton exchange membrane is mainly caused by free radical attack. Adding a free radical quencher is an effective way to improve chemical durability, but the introduction of transition metal compounds as free radical quenchers in the proton exchange membrane will reduce the electrochemical performance. Therefore, an improved solution of adding free radical quenchers in areas outside the proton exchange membrane is proposed. With the increase of power and current density, the gas diffusion layer in the membrane electrode will produce more liquid water, exacerbating the risk of electrode flooding. Therefore, it is necessary to improve the hydrophobicity of the gas diffusion layer and thus improve the transport of liquid water to ensure the transmission efficiency of the gas.
[0003] In the membrane electrode, the two sides of the catalyst layer are proton exchange membrane and gas diffusion layer respectively. CN100468853C proposes a method of loading a free radical quencher on one side or both sides or in the layer of the catalyst layer. The free radical quencher selected in this method includes small molecule organic compounds, manganese metal oxides, manganese salts and manganese complexes, which improves the chemical durability of the membrane electrode. In this patent, the organic small molecule compound has high mobility and is easy to lose in the membrane electrode, and the free radical quenching activity of the manganese metal compound is low, which has limited improvement on the durability of the membrane electrode. CN117117209A introduces cerium metal oxides and cerium salts as free radical quenchers into the gas diffusion layer, which improves the ability of the membrane electrode to quench free radicals and improves the durability of the membrane electrode. In this patent, metal oxides or metal salts are directly mixed with fluorine-containing polymer emulsions as microporous layer slurry, and the processing window is narrow. Fluoropolymer emulsions are sensitive to the pH value of the solvent. Metal oxides are highly alkaline, while metal salts with good solubility are highly acidic. The change in pH after the two are mixed can easily lead to emulsion demulsification, making subsequent processing impossible. Moreover, as inorganic materials, metal oxides and metal salts have poor compatibility with fluoropolymers, making it difficult to disperse them evenly and processing them more difficult. Some fluoropolymer emulsions contain ionic surfactants, which can also have an unknown effect on the stability of the emulsion when combined with metal cations.
[0004] Therefore, it is necessary to conduct in-depth research on the gas diffusion layer to improve the durability of the membrane electrode and thus improve the electrochemical performance of the fuel cell. Summary of the invention
[0005] The present invention is based on the inventor's discovery and understanding of the following facts and problems: In the related art, organic small molecule compounds, manganese metal oxides, manganese salts, manganese-based complexes, lanthanide metal oxides and lanthanide metal salts are introduced into the gas diffusion layer as free radical quenchers to improve the durability of the membrane electrode. However, organic small molecule compounds have high mobility and are easily lost in the membrane electrode; the free radical quenching ability of manganese-containing compounds is weaker than that of cerium-containing compounds; cerium metal oxides and cerium salts are easily mixed with fluorine-containing polymer emulsions to cause emulsion demulsification, and the compatibility of organic / inorganic materials is poor, which will reduce the molding quality of the microporous layer and the uniformity of the inorganic material dispersion, thereby reducing the mass transfer capacity of the gas diffusion layer. Therefore, it is necessary to study and improve the microporous layer and the gas diffusion layer.
[0006] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a microporous layer, which contains a cerium complex as a free radical quencher, which has good processability and dispersibility, can be evenly dispersed in the microporous layer, and the cerium complex used will not ionize anions and cations to affect the ion composition and pH value of the microporous layer slurry. The microporous layer not only has good gas-liquid transmission performance, but also has excellent free radical quenching ability, thereby improving the durability of the membrane electrode in the electrochemical device.
[0007] A microporous layer according to an embodiment of the present invention comprises: a hydrophobic material, a conductive material and a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce 3+ or Ce 4+ The ligand of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound.
[0008] Advantages and technical effects of the microporous layer of the embodiment of the present invention: 1. In the embodiment of the present invention, a cerium complex is used as a free radical quencher, and the ligand cyclodextrin compound has good dispersibility in water and is not easy to agglomerate and deposit during the molding process, thereby improving the dispersion uniformity of the free radical quencher cerium complex in the microporous layer, thereby improving the chemical stability of the membrane electrode; 2. In the embodiment of the present invention, the ligand crown ether compound can complex Ce ions in the center of the cyclic molecule to form a stable metal complex, which is beneficial to further improve the durability of the membrane electrode. At the same time, the crown ether ligand has excellent stability and dispersibility, and can meet The processing requirements of the microporous layer are met, the processing difficulty of the microporous layer and the gas diffusion layer is effectively reduced, and the molding quality is improved. In addition, the crown ether compound itself also has a free radical quenching effect. The crown ether has a synergistic effect after combining with the cerium ion to form a complex, which further enhances the free radical quenching property of the gas diffusion layer. 3. In the embodiment of the present invention, the use of the cerium complex as a free radical quencher will not ionize anions and cations to affect the ion composition and pH value of the microporous layer slurry. The microporous layer not only has good gas-liquid transmission performance, but also has excellent free radical quenching ability, thereby improving the durability of the membrane electrode in the electrochemical device.
[0009] In some embodiments, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl-β-cyclodextrin or water-soluble polymers of these cyclodextrin compounds;
[0010] Preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin or (2-hydroxypropyl)-β-cyclodextrin;
[0011] More preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.
[0012] In some embodiments, the crown ether compounds include 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4, 1,7-diaza-12-crown-4, triaza-12-crown-4, benzo-15-crown-5, cyclohexane-18-crown-6, cyclohexane-15-crown-5, 24-crown-8, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, 1-aza-15-crown -5, diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetra-15-crown-5-phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds;
[0013] Preferably, the crown ether compound includes at least one of 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5, 4,13-diaza-21-crown-7, dicyclohexyl-18-crown-6, 18-crown-6, 15-crown-5, 21-crown-7, 24-crown-8 or tetra-15-crown-5-phthalocyanine;
[0014] More preferably, the crown ether compound includes at least one of 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, dicyclohexyl-18-crown-6 ether, 15-crown-5 or 18-crown-6.
[0015] In some embodiments, the cerium complex includes at least one of a complex formed by cerium and a cyclodextrin compound and a complex formed by cerium and a crown ether compound.
[0016] In some embodiments, the complex formed by the cerium and the cyclodextrin compound includes: at least one of a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (IV)-carboxymethyl-β-cyclodextrin complex, a cerium (IV)-methyl-β-cyclodextrin complex, a cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, a cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex or a cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex.
[0017] In some embodiments, the complexes formed by the cerium and crown ether compounds include: cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown-5 complex, cerium (III)-diaza-18-crown-6 complex, cerium (III)-diaza-15-crown-5 complex, cerium (III)-4,10-diaza-15-crown-5 complex, cerium (III)-4,13-diaza-21-crown-7 complex, cerium (III) -At least one of dicyclohexyl-18-crown-6 ether complex, cerium (IV)-dicyclohexyl-18-crown-6 ether complex, cerium (III)-18-crown-6 complex, cerium (IV)-18-crown-6 complex, cerium (III)-15-crown-5 complex, cerium (III)-21-crown-7 complex, cerium (III)-24-crown-8 complex or cerium (IV)-tetra-15-crown-5-phthalocyanine complex.
[0018] In some embodiments, the cerium complex includes: at least one of: cerium (IV)-α-cyclodextrin complex, cerium (IV)-β-cyclodextrin complex, cerium (IV)-γ-cyclodextrin complex, cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown ether-5 complex, cerium (III)-diaza-18-crown ether-6 complex, cerium (III)-dicyclohexyl-18-crown-6 ether complex, cerium (III)-18-crown ether-6 complex, and cerium (III)-15-crown ether-5 complex.
[0019] In some embodiments, the cerium complex includes at least one of: a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (III)-1-aza-15-crown ether-5 complex, a cerium (III)-dicyclohexyl-18-crown-6 ether complex, and a cerium (III)-18-crown ether-6 complex.
[0020] In some embodiments, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is (10-200):(5-50):(0.1-10), preferably (10-100):(5-40):(0.1-5), and more preferably (10-60):(5-30):(0.1-1).
[0021] In some embodiments, the hydrophobic material includes at least one of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE); preferably at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer; more preferably polytetrafluoroethylene.
[0022] In some embodiments, the conductive material includes at least one of solid carbon, porous carbon, solid graphite, expanded graphite, conductive carbon black, and carbon nanotubes.
[0023] The embodiment of the present invention further provides a gas diffusion layer, comprising a substrate layer and a microporous layer, wherein the microporous layer is the microporous layer of the embodiment of the present invention. The gas diffusion layer of the embodiment of the present invention, in which a cerium complex is introduced as a free radical quencher in the microporous layer, not only has excellent free radical quenching ability, but also has good gas-liquid transmission performance.
[0024] In some embodiments, the base layer includes a carbon material layer and a hydrophobic material.
[0025] In some embodiments, the carbon material layer includes at least one of carbon paper, carbon cloth, carbon felt, and carbon black paper; preferably, the carbon material layer includes carbon paper, and further preferably, the average thickness of the carbon paper is 80-400 μm, the porosity is 50-95%, and the average pore size is 10-100 μm; preferably, the average thickness of the carbon paper is 110-360 μm, the porosity is 60%-90%, and the average pore size is 15-90 μm; more preferably, the average thickness of the carbon paper is 140-320 μm, the porosity is 70%-85%, and the average pore size is 20-80 μm.
[0026] In some embodiments, the hydrophobic material includes at least one of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE); preferably at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer; more preferably polytetrafluoroethylene.
[0027] In some embodiments, the average thickness of the microporous layer is 10-70 μm, and the average pore size is 0.05-2 μm; preferably, the average thickness of the microporous layer is 15-60 μm, and the average pore size is 0.05-0.8 μm; more preferably, the average thickness of the microporous layer is 15-45 μm, and the average pore size is 0.08-0.5 μm;
[0028] In some embodiments, the average thickness of the base layer is 80-400 μm, the porosity is 50-95%, and the average pore size is 10-100 μm; preferably, the average thickness of the base layer is 110-360 μm, the porosity is 60%-90%, and the average pore size is 15-90 μm; more preferably, the average thickness of the base layer is 140-320 μm, the porosity is 70%-85%, and the average pore size is 20-80 μm.
[0029] In some embodiments, the base layer further comprises a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce. 3+ or Ce 4+The ligand of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound. Wherein, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl-β-cyclodextrin or water-soluble polymers of these cyclodextrin compounds; the crown ether compound includes 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4-ether, 1,7-diaza-12-crown-4, triaza- 12-crown-4, benzo-15-crown-5, cyclohexanedo-18-crown-6, cyclohexanedo-15-crown-5, 24-crown-8-ether, dicyclohexanedo-24-crown-8, dicyclohexyl-18-crown-6 ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetra-15-crown-5-phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds. Preferably, the cerium complex includes a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (IV)-carboxymethyl-β-cyclodextrin complex, a cerium (IV)-methyl-β-cyclodextrin complex, a cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, a cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex or a cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex, a cerium (III)-1-aza-18-crown-6-ether complex, a cerium (III)-1-aza-15-crown-5-ether complex, a cerium (III)-diaza-1 At least one of a cerium (III)-8-crown-6 complex, a cerium (III)-4,10-diaza-15-crown-5-ether complex, a cerium (III)-4,13-diaza-21-crown-7 complex, a cerium (III)-dicyclohexyl-18-crown-6 ether complex, a cerium (IV)-dicyclohexyl-18-crown-6 ether complex, a cerium (III)-18-crown-6 complex, a cerium (IV)-18-crown-6 complex, a cerium (III)-15-crown-5 complex, a cerium (III)-21-crown-7 complex, a cerium (III)-24-crown-8 complex or a cerium (IV)-tetra-15-crown-5-phthalocyanine complex.
[0030] In some embodiments, in the base layer, the mass ratio of the carbon material layer, the hydrophobic material and the free radical quencher is 100:(1-50):(0-10), preferably 100:(3-30):(0-9), and more preferably 100:(5-25):(0-5).
[0031] An embodiment of the present invention also provides a method for preparing a gas diffusion layer, comprising the following steps: dispersing and mixing a hydrophobic material, a free radical quencher, a conductive material and a surfactant in a solvent to obtain a microporous layer slurry, coating the microporous layer slurry on a base layer, and obtaining a gas diffusion layer through drying and heat treatment.
[0032] In some embodiments, the method for preparing the base layer comprises: impregnating the carbon material layer in a hydrophobic modified impregnation liquid, drying, and heat treating to obtain the base layer, wherein the hydrophobic modified impregnation liquid comprises a hydrophobic material and a solvent;
[0033] Optionally, the hydrophobically modified impregnation liquid further comprises at least one of a free radical quencher or a surfactant; preferably, in the hydrophobically modified impregnation liquid, the mass ratio of the solvent, the hydrophobic material, the free radical quencher and the surfactant is 100:(0.4-20):(0-4):(0-4), more preferably 100:(1-10):(0-3):(0-3), and even more preferably 100:(2-10):(0-2):(0-2);
[0034] Optionally, the solvent includes water. Preferably, the solvent also includes a lower aliphatic alcohol, and the lower aliphatic alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol, and / or, in the solvent, the mass ratio of water to the lower aliphatic alcohol is 1:(0-4);
[0035] Optionally, the immersion time is 1 to 30 minutes;
[0036] Optionally, the drying method includes air drying or freeze drying. Preferably, the air drying temperature is 50 to 150° C., and the time is 3 to 60 minutes; the freeze drying temperature is -80° C. to 0° C., and the time is 4 to 48 hours;
[0037] Optionally, the heat treatment temperature is 240-400° C., and the time is 1-10 min.
[0038] In some embodiments, the solvent includes water. Preferably, the solvent also includes a lower fatty alcohol, and the lower fatty alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol; and / or, in the solvent, the mass ratio of water to the lower fatty alcohol is 1:(0-4).
[0039] In some embodiments, in the microporous layer slurry, the mass percentage of the surfactant is 0.1-15%, preferably 0.5-10%, and more preferably 1-8%.
[0040] In some embodiments, the coating includes at least one of blade coating, slit coating, roller coating, extrusion coating, micro-concave transfer coating or spray coating, preferably blade coating, slit coating or spray coating; further preferably, the nozzle of the spray coating is selected from one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle or an electrostatic nozzle, more preferably an ultrasonic nozzle.
[0041] In some embodiments, the drying method includes at least one of forced air drying or freeze drying; preferably, the forced air drying temperature is 50-150°C, and the time is 3-60 minutes; the freeze drying temperature is -80°C-0°C, and the time is 4-48 hours.
[0042] In some embodiments, the heat treatment temperature is 250-400° C., and the time is 1-10 min.
[0043] The embodiment of the present invention further provides a membrane electrode, comprising the gas diffusion layer of the embodiment of the present invention or the gas diffusion layer manufactured by the method of the embodiment of the present invention.
[0044] The membrane electrode of the embodiment of the present invention includes the gas diffusion layer of the embodiment of the present invention, which has all the advantages brought by the gas diffusion layer of the embodiment of the present invention, and will not be described in detail here.
[0045] In some embodiments, the membrane electrode further includes a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer, the anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the proton exchange membrane, and the gas diffusion layer is arranged on the side of the anode catalyst layer and the cathode catalyst layer away from the proton exchange membrane.
[0046] An embodiment of the present invention further provides a fuel cell, comprising the membrane electrode according to the embodiment of the present invention.
[0047] The fuel cell of the embodiment of the present invention includes the membrane electrode of the embodiment of the present invention, which has all the advantages brought by the membrane electrode of the embodiment of the present invention, and will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 It is the water contact angle test diagram of the substrate layer prepared in Examples 3 and 4.
[0049] Figure 2 It is a water contact angle test diagram of the microporous layer prepared in Examples 11-13 and Comparative Examples 2-3. DETAILED DESCRIPTION
[0050] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0051] A microporous layer according to an embodiment of the present invention comprises: a hydrophobic material, a conductive material and a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce 3+ or Ce 4+ The ligand of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound.
[0052] The microporous layer of the embodiment of the present invention adopts a cerium complex as a free radical quencher, and the ligand cyclodextrin compound has good dispersibility in water and is not easy to agglomerate and deposit during the molding process, which effectively reduces the processing difficulty of the microporous layer and improves the dispersion uniformity of the free radical quencher cerium complex in the microporous layer, thereby improving the chemical stability of the membrane electrode; in the embodiment of the present invention, the ligand crown ether compound can complex Ce ions in the center of the cyclic molecule to form a stable metal complex, which is beneficial to further improve the durability of the membrane electrode. At the same time, the crown ether ligand has excellent stability and dispersibility, which can meet the requirements of the microporous layer. The processing requirements of the layer are effectively reduced, the processing difficulty of the microporous layer and the gas diffusion layer is improved, and the molding quality is improved. In addition, the crown ether compound itself also has a free radical quenching effect. The crown ether has a synergistic effect after combining with the cerium ion to form a complex, which further enhances the free radical quenching property of the gas diffusion layer. In the embodiment of the present invention, the use of the cerium complex as a free radical quencher will not ionize anions and cations to affect the ion composition and pH value of the microporous layer slurry. The microporous layer not only has good gas-liquid transmission performance, but also has excellent free radical quenching ability, thereby improving the durability of the membrane electrode in the electrochemical device.
[0053] In some embodiments, the cyclodextrin compounds include α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl Preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin or (2-hydroxypropyl)-β-cyclodextrin; More preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin. In the embodiment of the present invention, the ligand adopts the preferred cyclodextrin compound, which is conducive to further improving the dispersibility of the free radical quencher in the microporous layer and reducing the processing difficulty of the gas diffusion layer.
[0054] In some embodiments, the crown ether compounds include 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4, 1,7-diaza-12-crown-4, triaza-12-crown-4, benzo-15-crown-5, cyclohexane-18-crown-6, cyclohexane-15-crown-5, 24-crown-8, dicyclohexane-24-crown-8, dicyclohexyl -18-crown-6 ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetra-15-crown-5- Phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds; preferably, the crown ether compounds include 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5, 4,13-diaza-21-crown-7, dicyclohexyl-18-crown-6, 18-crown-6, 1 At least one of 5-crown-5, 21-crown-7, 24-crown-8-ether or tetra-15-crown-5-phthalocyanine; more preferably, the crown ether compound includes at least one of 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, dicyclohexyl-18-crown-6 ether, 15-crown-5 or 18-crown-6. In the embodiment of the present invention, a preferred crown ether compound is used as a ligand, and the hole size at the center of the molecule matches the size of the Ce ion, which is conducive to the formation of a stable metal complex, thereby further improving the durability of the membrane electrode.
[0055] In some embodiments, the cerium complex includes at least one of a complex formed by cerium and a cyclodextrin compound and a complex formed by cerium and a crown ether compound.
[0056] In some embodiments, the complex formed by the cerium and the cyclodextrin compound includes: at least one of a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (IV)-carboxymethyl-β-cyclodextrin complex, a cerium (IV)-methyl-β-cyclodextrin complex, a cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, a cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex or a cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex.
[0057] In some embodiments, the complexes formed by the cerium and crown ether compounds include: cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown-5 complex, cerium (III)-diaza-18-crown-6 complex, cerium (III)-diaza-15-crown-5 complex, cerium (III)-4,10-diaza-15-crown-5 complex, cerium (III)-4,13-diaza-21-crown-7 complex, cerium (III) -At least one of dicyclohexyl-18-crown-6 ether complex, cerium (IV)-dicyclohexyl-18-crown-6 ether complex, cerium (III)-18-crown-6 complex, cerium (IV)-18-crown-6 complex, cerium (III)-15-crown-5 complex, cerium (III)-21-crown-7 complex, cerium (III)-24-crown-8 complex or cerium (IV)-tetra-15-crown-5-phthalocyanine complex.
[0058] In some embodiments, the cerium complex includes: at least one of cerium (IV)-α-cyclodextrin complex, cerium (IV)-β-cyclodextrin complex, cerium (IV)-γ-cyclodextrin complex, cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown-5 complex, cerium (III)-diaza-18-crown-6 complex, cerium (III)-dicyclohexyl-18-crown-6 ether complex, cerium (III)-18-crown-6 complex, and cerium (III)-15-crown-5 complex; preferably at least one of cerium (IV)-α-cyclodextrin complex, cerium (IV)-β-cyclodextrin complex, cerium (III)-1-aza-15-crown-5 complex, cerium (III)-dicyclohexyl-18-crown-6 ether complex, and cerium (III)-18-crown-6 complex.
[0059] The cerium complexes of the embodiments of the present invention, among the complexes formed by cerium ions and cyclodextrin, α-cyclodextrin and β-cyclodextrin have low costs and large outputs, and have obvious cost advantages; among the complexes formed by cerium ions and crown ethers, trivalent cerium ions have better chemical stability than tetravalent cerium ions; azacrown ethers are easier to react with cerium salts to obtain complexes, and have good stability; 18-crown-6 has a suitable size compared with crown ethers with more or fewer main chain atoms, is more conducive to the complexation of cerium ions, is easy to prepare, and the cerium complex has good stability; crown ethers with cyclohexyl substituents have good solubility in water and fatty alcohols, which is beneficial to the processing and preparation of the microporous layer and the substrate layer.
[0060] In some embodiments, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is (10-200): (5-50): (0.1-10), preferably (10-100): (5-40): (0.1-5), and more preferably (10-60): (5-30): (0.1-1). In the embodiments of the present invention, the preferred ratio of each material is used to further improve the performance of the microporous layer, so that the prepared gas diffusion layer not only has excellent free radical quenching performance, but also has excellent gas-liquid transmission performance. If too little free radical quencher is added, the free radical quenching effect will not be obvious. If too much free radical quencher is added, it will affect the pore structure and gas transmission characteristics of the GDL, which is not conducive to improving its conductivity and gas permeability, thereby affecting the performance of the fuel cell; some free radical quenchers may diffuse into the catalyst layer and react with the catalyst, causing catalyst poisoning or deactivation; at the same time, free radical quenchers are usually expensive, and excessive use will increase the manufacturing cost of the fuel cell; under certain high-temperature operating conditions, excessive quenchers may cause additional thermal effects, which is not conducive to temperature control.
[0061] In some embodiments, the hydrophobic material includes polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), ethylene-chlorotrifluoroethylene copolymer (ECTFE) at least one; preferably polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer at least one; more preferably polytetrafluoroethylene. In the embodiment of the present invention, there is no particular restriction on the hydrophobic material, and the hydrophobic materials commonly used in the prior art are all applicable to the present invention.
[0062] In some embodiments, the conductive material includes at least one of solid carbon, porous carbon, solid graphite, expanded graphite, conductive carbon black, and carbon nanotubes. In the embodiments of the present invention, there is no particular limitation on the conductive material, and the conductive materials commonly used in the prior art are applicable to the present invention.
[0063] The embodiment of the present invention further provides a gas diffusion layer, comprising a substrate layer and a microporous layer, wherein the microporous layer is the microporous layer of the embodiment of the present invention.
[0064] The gas diffusion layer of the embodiment of the present invention introduces a cerium complex as a free radical quencher in the microporous layer, which not only has excellent free radical quenching ability but also has good gas-liquid transmission performance.
[0065] In some embodiments, the base layer includes a carbon material layer and a hydrophobic material.
[0066] In some embodiments, the carbon material layer includes at least one of carbon paper, carbon cloth, carbon felt, and carbon black paper; preferably, the carbon material layer includes carbon paper, and further preferably, the average thickness of the carbon paper is 80-400 μm, the porosity is 50-95%, and the average pore size is 10-100 μm; preferably, the average thickness of the carbon paper is 110-360 μm, the porosity is 60%-90%, and the average pore size is 15-90 μm; more preferably, the average thickness of the carbon paper is 140-320 μm, the porosity is 70%-85%, and the average pore size is 20-80 μm.
[0067] In some embodiments, the hydrophobic material includes at least one of polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE), tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer (THV), polyvinyl fluoride (PVF), polychlorotrifluoroethylene (PCTFE), and ethylene-chlorotrifluoroethylene copolymer (ECTFE); preferably at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer; more preferably polytetrafluoroethylene.
[0068] In some embodiments, the average thickness of the microporous layer is 10-70 μm, and the average pore size is 0.05-2 μm; preferably, the average thickness of the microporous layer is 15-60 μm, and the average pore size is 0.05-0.8 μm; more preferably, the average thickness of the microporous layer is 15-45 μm, and the average pore size is 0.08-0.5 μm.
[0069] In some embodiments, the average thickness of the base layer is 80-400 μm, the porosity is 50-95%, and the average pore size is 10-100 μm; preferably, the average thickness of the base layer is 110-360 μm, the porosity is 60%-90%, and the average pore size is 15-90 μm; more preferably, the average thickness of the base layer is 140-320 μm, the porosity is 70%-85%, and the average pore size is 20-80 μm.
[0070] In some embodiments, the base layer further comprises a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce. 3+ or Ce4+ At least one of the ligands of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound;
[0071] Wherein, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl-β-cyclodextrin or water-soluble polymers of these cyclodextrin compounds;
[0072] The crown ether compounds include 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4, 1,7-diaza-12-crown-4, triaza-12-crown-4, benzo-15-crown-5, cyclohexane-18-crown-6, cyclohexane-15-crown-5, 24-crown-8, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, 1-aza-15-crown-5, dicyclohexane-18-crown-6, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, dicyclohexyl-18-crown-5, dicyclohexane-18-crown-6, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, dicyclohexyl-18-crown-6, dicyclohexane ... Aza-18-crown-6, 4,10-diaza-15-crown-5-ether, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetrakis-15-crown-5-phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds.
[0073] Preferably, the cerium complex includes cerium (IV)-α-cyclodextrin complex, cerium (IV)-β-cyclodextrin complex, cerium (IV)-γ-cyclodextrin complex, cerium (IV)-carboxymethyl-β-cyclodextrin complex, cerium (IV)-methyl-β-cyclodextrin complex, cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex, cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex, cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown-5-ether complex, cerium (III)-diaza-1 At least one of a cerium (III)-8-crown-6 complex, a cerium (III)-4,10-diaza-15-crown-5-ether complex, a cerium (III)-4,13-diaza-21-crown-7 complex, a cerium (III)-dicyclohexyl-18-crown-6 ether complex, a cerium (IV)-dicyclohexyl-18-crown-6 ether complex, a cerium (III)-18-crown-6 complex, a cerium (IV)-18-crown-6 complex, a cerium (III)-15-crown-5 complex, a cerium (III)-21-crown-7 complex, a cerium (III)-24-crown-8 complex or a cerium (IV)-tetra-15-crown-5-phthalocyanine complex.
[0074] In some embodiments, in the base layer, the mass ratio of the carbon material layer, the hydrophobic material and the free radical quencher is 100:(1-50):(0-10), preferably 100:(3-30):(0-9), and more preferably 100:(5-25):(0-5).
[0075] An embodiment of the present invention also provides a method for preparing a gas diffusion layer, comprising the following steps: dispersing and mixing a hydrophobic material, a free radical quencher, a conductive material and a surfactant in a solvent to obtain a microporous layer slurry, coating the microporous layer slurry on a base layer, and obtaining a gas diffusion layer through drying and heat treatment.
[0076] In some embodiments, the solvent includes water. Preferably, the solvent also includes a lower fatty alcohol, and the lower fatty alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol; and / or, in the solvent, the mass ratio of water to the lower fatty alcohol is 1:(0-4).
[0077] In some embodiments, in the microporous layer slurry, the mass percentage of the surfactant is 0.1-15%, preferably 0.5-10%, and more preferably 1-8%. In the embodiment of the present invention, during the preparation of the microporous layer slurry, the conductive material and the hydrophobic material have poor compatibility, and the addition of a surfactant is beneficial to improving the mixing effect and slurry stability. The embodiment of the present invention has no particular restrictions on the surfactant, and nonionic surfactants commonly used in the prior art can be used, such as Triton X100, fatty alcohol polyoxyethylene ether, fatty acid glyceride, polysorbate, preferably Triton X100.
[0078] In some embodiments, the coating includes at least one of blade coating, slit coating, roller coating, extrusion coating, micro-concave transfer coating or spray coating, preferably blade coating, slit coating or spray coating; further preferably, the nozzle of the spray coating is selected from one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle or an electrostatic nozzle, more preferably an ultrasonic nozzle. In the embodiment of the present invention, ultrasonic spray is preferably used, which has high atomization quality, controllable atomized droplet particle size, and is independent of fluid pressure, and the obtained microporous layer has good consistency.
[0079] In some embodiments, the drying method includes at least one of blast drying or freeze drying; preferably, the blast drying temperature is 50 to 150°C, and the time is 3 to 60 minutes; the freeze drying temperature is -80°C to 0°C, and the time is 4 to 48 hours. The heat treatment temperature is 250 to 400°C, and the time is 1 to 10 minutes. In an embodiment of the present invention, the solvent is removed by a drying process to form a solid structure. Heat treatment after drying can change the physical structure of the hydrophobic material so that the crystal form of the hydrophobic material changes. For example, common commercial PTFE needs to be heat treated above 240°C to transform the low-temperature crystal form into a high-temperature crystal form. The transformation of the crystal form can improve the mechanical strength, rigidity and solvent resistance of the hydrophobic material.
[0080] In some embodiments, the method for preparing the base layer comprises: impregnating the carbon material layer in a hydrophobic modified impregnation liquid, and obtaining the base layer after drying and heat treatment.
[0081] Wherein, the hydrophobic modified impregnation liquid comprises a hydrophobic material and a solvent; further, the hydrophobic modified impregnation liquid further comprises at least one of a free radical quencher or a surfactant; preferably, in the hydrophobic modified impregnation liquid, the mass ratio of the solvent, the hydrophobic material, the free radical quencher and the surfactant is 100:(0.4-20):(0-4):(0-4), more preferably 100:(1-10):(0-3):(0-3), and more preferably 100:(2-10):(0-2):(0-2);
[0082] The surfactant is selected from the nonionic surfactant commonly used in the prior art, such as Triton X100, fatty alcohol polyoxyethylene ether, fatty acid glyceride, polysorbate, preferably Triton X100;
[0083] The solvent includes water. Preferably, the solvent also includes a lower fatty alcohol, and the lower fatty alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol; in the solvent, the mass ratio of water to the lower fatty alcohol is 1:(0-4).
[0084] In some embodiments, the immersion time is 1 to 30 minutes; the drying method includes air drying or freeze drying. Preferably, the air drying temperature is 50 to 150°C and the time is 3 to 60 minutes; the freeze drying temperature is -80°C to 0°C and the time is 4 to 48 hours; the heat treatment temperature is 240 to 400°C and the time is 1 to 10 minutes.
[0085] In an embodiment of the present invention, a cerium complex is introduced into a base layer and / or a microporous layer as a free radical quencher to prepare a gas diffusion layer. The introduction of the metal complex gives the gas diffusion layer an excellent free radical quenching function. When the gas diffusion layer is applied to a membrane electrode, it can quench the free radicals generated by the electrochemical reaction, improve the chemical stability of the ion exchange resin in the proton exchange membrane and the catalyst layer, and thus improve the durability of the membrane electrode. The gas diffusion layer of the embodiment of the present invention can also be used in the fields of filtration and separation.
[0086] The embodiment of the present invention further provides a membrane electrode, comprising the gas diffusion layer of the embodiment of the present invention or the gas diffusion layer manufactured by the method of the embodiment of the present invention.
[0087] The membrane electrode of the embodiment of the present invention includes the gas diffusion layer of the embodiment of the present invention, which has all the advantages brought by the gas diffusion layer of the embodiment of the present invention, which will not be repeated here. The membrane electrode of the embodiment of the present invention can be used in the fields of fuel cells, water electrolysis and hydrogen production.
[0088] In some embodiments, the membrane electrode further includes a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer, the anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the proton exchange membrane, and the gas diffusion layer is arranged on the side of the anode catalyst layer and the cathode catalyst layer away from the proton exchange membrane.
[0089] An embodiment of the present invention further provides a fuel cell, comprising the membrane electrode according to the embodiment of the present invention.
[0090] The present invention is described in detail below with reference to the embodiments and the accompanying drawings.
[0091] In the embodiments of the present invention, the raw materials, equipment, etc. involved, unless otherwise specified, are all raw materials and equipment that can be made by commercial channels or known methods.
[0092] The performance testing methods involved in each embodiment and comparative example are as follows:
[0093] 1. Pore size test: The test method is the bubble pressure method (gas-liquid displacement technology), and the test instrument is the Porometer3G pore size analyzer. The wet-first-dry mode is adopted, that is, the sample is fully wetted with a liquid that can be infiltrated with it, and then a pressure difference is applied to both sides of the membrane to overcome the surface tension of the infiltrating liquid in the membrane pores, and the infiltrating liquid is driven through the pores to obtain the pore size distribution of the sample.
[0094] The gas source is compressed air and nitrogen, and the test area is 3.14cm 2 .
[0095] Each time, 3 to 5 groups of samples were taken for parallel experiments.
[0096] 2. Porosity test: The test method is mercury intrusion method, and the test equipment is AutoPore V 9605 mercury intrusion instrument. Under the action of external pressure, mercury is injected into the pores of the sample. As the pressure gradually increases, mercury can penetrate into smaller pores. By measuring the volume of injected mercury under different pressures, the pore size distribution and porosity of the sample can be calculated.
[0097] 3. Contact angle test: The sessile drop method is used, the liquid drop is water, and the solid sample is the gas diffusion layer or substrate layer. The contact angle between the liquid drop and the solid sample is measured for 16 seconds. The larger the contact angle, the better the hydrophobicity.
[0098] 4. Vertical resistance of gas diffusion layer (GDL): The test method refers to GB / T20042.7-2022 "Proton exchange membrane fuel cell part 7: carbon paper characteristics test method" to conduct GDL vertical resistance test, and the test pressure is 1MPa. The smaller the vertical resistance, the more conducive to improving membrane electrode performance.
[0099] 5. Permeability of gas diffusion layer: Use a pore size analyzer to test the flow rate of N2 through different gas diffusion layers at a pressure difference of 5 kPa. The larger the flow rate, the better the gas mass transfer capacity of the gas diffusion layer.
[0100] 6. Fuel cell polarization curve, voltage and hydrogen permeation current: The test method refers to GB / T20042.5-2022 "Proton Exchange Membrane Fuel Cell Part 5: Membrane Electrode Test Method". The test temperature for polarization curve, voltage and hydrogen permeation current is 80°C and the relative humidity is 80%. The battery voltage is 1.5A / cm 2Voltage under current density. Voltage decay is an important means to characterize the durability of membrane electrode. Under the same test conditions, the less voltage decay, the better the durability of membrane electrode. Hydrogen permeation current reflects the barrier property of membrane electrode. The smaller the hydrogen permeation current, the better the barrier property and the better the durability of membrane electrode.
[0101] 7. Membrane electrode preparation method: Cut the proton exchange membrane into 5*5cm size, use an electrostatic sprayer to evenly spray Pt / C catalyst on both sides of the membrane to prepare CCM (fuel cell chip), and the loading of the anode and cathode is 0.5mg / cm 2 The gas diffusion layer is pressed on both sides of the CCM by hot pressing to prepare MEA (membrane electrode). The single cell test system is used for online detection, with the anode and cathode gas flow rate of 800 mL / min and the back pressure of 0.2 MPa.
[0102] 1. Preparation of cerium complex
[0103] Example 1 Preparation of Ce(IV)-Cyclodextrin Complex
[0104] An equal volume (30 mL) of 20 mmol / L cerium ammonium nitrate and 20 mmol / L cyclodextrin compound ligand aqueous solution were mixed, stirred for reaction for 4 h, precipitated and washed with ethanol, and vacuum dried to obtain a cyclodextrin compound complex of cerium (IV).
[0105] Example 2 Preparation of Ce(III)-Crown Ether Complex
[0106] Dissolve 0.5mmol of crown ether compound ligand in 5mL of ethyl acetate, and dissolve 0.5mmol of cerium nitrate hexahydrate in 5mL of ethyl acetate. Add 15 drops of triethyl orthoformate to the ligand solution and cerium nitrate hexahydrate solution respectively, reflux for 5h, and slowly add the ethyl acetate solution of the ligand to the ethyl acetate solution of cerium nitrate hexahydrate after cooling, and a white precipitate is immediately observed. After continuous stirring for 2h, filter the white precipitate, wash with ethyl acetate, and vacuum dry to obtain the crown ether compound complex of cerium (III).
[0107] The coordination centers and organic ligands of the cerium complexes prepared in Example 1 and Example 2 are shown in Table 1.
[0108] Table 1
[0109]
[0110] 2. Preparation of the base layer
[0111] Example 3
[0112] Carbon paper (CP-1) was used as the carbon material layer, and the average thickness of the carbon paper was 191 μm, the porosity was 80.3%, and the average pore size was 64.7 μm.
[0113] The carbon paper CP-1 was immersed in an impregnation solution, in which the mass percentage of the hydrophobic material polytetrafluoroethylene was 10% and the rest was solvent water. The solution was immersed for 10 minutes, dried at 80°C for 15 minutes, and then heat treated at 300°C for 5 minutes to obtain a modified hydrophobic base layer MCP-1.
[0114] Example 4
[0115] The preparation method is the same as that of Example 3, except that the impregnation solution includes solvent water, hydrophobic material polytetrafluoroethylene and the cerium complex MC-1 prepared in Example 1, wherein the mass content of polytetrafluoroethylene is 10%, and the mass content of the cerium complex MC-1 is 1%, to obtain the base layer MCP-2.
[0116] Example 5
[0117] Carbon paper (CP-3) was used as the carbon material layer, and the average thickness of the carbon paper was 103 μm, the porosity was 52.7%, and the average pore size was 34.6 μm.
[0118] The carbon paper CP-3 was immersed in an impregnation solution, which included 40wt% water, 25wt% ethanol, 15wt% isopropanol, 10wt% n-propanol, 8wt% hydrophobic material polytetrafluoroethylene, 0.1wt% cerium complex MC-3 and 1.9wt% Triton X100, immersed for 5 minutes, dried at 150°C for 5 minutes, and then heat treated at 400°C for 2 minutes to obtain a modified hydrophobic base layer MCP-3.
[0119] Example 6
[0120] Carbon paper (CP-4) is used as the carbon material layer, and the average thickness of the carbon paper is 152 μm, the porosity is 82.2%, and the average pore size is 76.2 μm.
[0121] The carbon paper CP-4 was immersed in an impregnation solution comprising 60wt% water, 30wt% tert-butyl alcohol, 5wt% polytetrafluoroethylene and 5wt% Triton X100, immersed for 5 minutes, frozen at -30°C for 2 hours, freeze-dried at -10°C for 24 hours to remove volatiles, and then heat treated at 320°C for 10 minutes to obtain a modified hydrophobic base layer MCP-4.
[0122] The average thickness, average pore size and porosity of the base layer prepared in Examples 3-6 are shown in Table 2.
[0123] Table 2
[0124] Carbon Materials Basal layer Average thickness (μm) Average pore size (μm) Porosity (%) CP-1 CP-1 —— 191 64.7 80.3 Example 3 CP-1 MCP-1 192 63.7 78.9 Example 4 CP-1 MCP-2 192 63.8 78.8 CP-3 CP-3 —— 103 34.6 52.7 Example 5 CP-3 MCP-3 105 32.5 48.3 CP-4 CP-4 —— 152 76.2 82.2 Example 6 CP-4 MCP-4 155 72.2 80.1
[0125] It can be seen from Table 2 that the thickness, average pore size and porosity of the base layer of the hydrophobically modified carbon paper are slightly different from those of the untreated carbon paper.
[0126] Figure 1 is the water contact angle of Example 3, Example 4 and carbon paper CP-1, Figure 1 It can be seen that in Example 3, the carbon paper was hydrophobically modified by adding PTFE as a hydrophobic material, which effectively improved the hydrophobicity of the base layer. In Example 4, a free radical quencher cerium complex was further added on the basis of Example 3, which had no adverse effect on the hydrophobicity of the base layer and was slightly improved compared with the hydrophobic performance of Example 3.
[0127] 3. Preparation of Gas Diffusion Layer
[0128] Example 7
[0129] PTFE, water, free radical quencher MC-2, conductive carbon black and Triton X100 are mixed to obtain a microporous layer slurry, in which the water content is 75wt%, the PTFE content is 6wt%, the free radical quencher content is 0.8wt%, the conductive carbon black content is 12wt%, and the Triton X100 content is 6.2wt%.
[0130] The microporous layer slurry was coated on one side of the base layer MCP-1 in Example 3 by doctor blade coating, dried at 80° C. for 15 min, and then heat treated at 340° C. for 5 min to obtain a gas diffusion layer GDL-1A.
[0131] In the microporous layer of the gas diffusion layer prepared in this embodiment, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is 12:6:0.8.
[0132] Example 8
[0133] PTFE, water, free radical quencher MC-3, conductive carbon black and Triton X100 are mixed to obtain a microporous layer slurry, in which the water content is 85wt%, the PTFE content is 3%, the free radical quencher content is 0.03wt%, the conductive carbon black content is 5wt%, and the Triton X100 content is 6.97wt%.
[0134] The microporous layer slurry was coated on one side of the base layer MCP-2 in Example 4 by doctor blade coating, dried at 100° C. for 10 min, and then heat treated at 350° C. for 5 min to obtain a gas diffusion layer GDL-2B.
[0135] In the microporous layer of the gas diffusion layer prepared in this embodiment, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is 50:30:0.3.
[0136] Example 9
[0137] PTFE, solvent, free radical quencher MC-4, conductive carbon black and Triton X100 are mixed to obtain a microporous layer slurry, in which the solvent content is 90wt%, the PTFE content is 3%, the free radical quencher content is 0.06wt%, the conductive carbon black content is 5.5wt%, and the Triton X100 content is 1.44wt%, wherein the solvent is a mixed solvent of water and ethanol in a mass ratio of 4:1.
[0138] The microporous layer slurry was coated on one side of the base layer MCP-3 in Example 5 by doctor blade coating, dried at 60° C. for 20 min, and then heat treated at 360° C. for 3 min to obtain a gas diffusion layer GDL-3C.
[0139] In the microporous layer of the gas diffusion layer prepared in this embodiment, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is 55:30:0.6.
[0140] Example 10
[0141] PTFE, solvent, free radical quencher MC-5, conductive carbon black and Triton X100 are mixed to obtain a microporous layer slurry, in which the solvent content is 95wt%, the PTFE content is 0.8%, the free radical quencher content is 0.01wt%, the conductive carbon black content is 1.5wt%, and the Triton X100 content is 2.69wt%, wherein the solvent is a mixed solvent of water and tert-butanol in a mass ratio of 1:2.
[0142] The microporous layer slurry was coated on one side of the base layer MCP-4 in Example 6 by doctor blade coating, dried at 140° C. for 5 min, and then heat treated at 360° C. for 4 min to obtain a gas diffusion layer GDL-4D-1.
[0143] In the microporous layer of the gas diffusion layer prepared in this embodiment, the mass ratio of the conductive material, the hydrophobic material and the free radical quencher is 15:8:0.1.
[0144] Embodiment 11
[0145] The method is the same as that of Example 10, except that the microporous layer slurry is coated by spray coating using an ultrasonic nozzle to obtain a gas diffusion layer GDL-4D-2.
[0146] Example 12
[0147] The method is the same as that of Example 10, except that the drying method adopted after the microporous layer slurry is coated is freeze drying, the drying temperature is -5°C, and the drying time is 36 hours, to obtain a gas diffusion layer GDL-4D-3.
[0148] Example 13
[0149] The method is the same as that of Example 10, except that the base layer material uses the carbon paper CP-4 in Example 4 that has not been hydrophobically modified to obtain the gas diffusion layer GDL-4D-4.
[0150] Comparative Example 1
[0151] The method is the same as that of Example 7, except that the free radical quencher MC-2 is not added to the microporous layer slurry to obtain a gas diffusion layer D-GDL-1.
[0152] Comparative Example 2
[0153] The method is the same as that of Example 10, except that the free radical quencher MC-5 is not added to the microporous layer slurry to obtain a gas diffusion layer D-GDL-4-1.
[0154] Comparative Example 3
[0155] The method is the same as that of Example 12, except that the free radical quencher MC-5 is not added to the microporous layer slurry to obtain a gas diffusion layer D-GDL-4-3.
[0156] Comparative Example 4
[0157] The method is the same as that of Example 10, except that the free radical quencher used in the microporous layer slurry is cerium oxide with a particle size of 20 to 50 nm, and a gas diffusion layer D4-D-GDL-4-1 is obtained.
[0158] The average thickness and pore size of the microporous layer in the gas diffusion layers prepared in Examples 7-13 and Comparative Examples 1-4 are shown in Table 3.
[0159] Table 3
[0160] Gas Diffusion Layer Average thickness (μm) Average pore size (nm) Example 7 GDL-1A 25 82 Example 8 GDL-2B 15 106 Example 9 GDL-3C 40 452 Example 10 GDL-4D-1 25 276 Embodiment 11 GDL-4D-2 25 285 Example 12 GDL-4D-3 25 307 Example 13 GDL-4D-4 25 287 Comparative Example 1 D-GDL-1 25 79 Comparative Example 2 D-GDL-4-1 25 273 Comparative Example 3 D-GDL-4-3 25 315 Comparative Example 4 D4-D-GDL-4-1 25 243
[0161] The gas diffusion layers prepared in Examples 7-13 and Comparative Examples 1-4 were subjected to performance tests. The test results are shown in Tables 4 and Figure 2 .
[0162] Table 4
[0163]
[0164]
[0165] Figure 2 The contact angle images of the microporous layers of GDL-4D-1 of Example 10, GDL-4D-2 of Example 11, GDL-4D-3 of Example 12, D-GDL-4-1 of Comparative Example 2, and D-GDL-4-3 of Comparative Example 3 are shown. Figure 2It can be seen that when the free radical quencher is not added to the microporous layer slurry, the free radical quencher is compared with Example 10 in which the free radical quencher is added, and when the free radical quencher is not added to the microporous layer slurry, the free radical quencher is compared with Example 12 in which the free radical quencher is added, the free radical quencher will not have an adverse effect on the surface hydrophobicity of the microporous layer, and the addition of the free radical quencher will slightly improve the surface hydrophobicity of the microporous layer. It can be seen from Example 12 and Example 10 that the drying treatment by freeze drying after coating can improve the uniformity and surface smoothness of the microporous layer, and Example 12 shows better surface hydrophobicity. It can be seen from Example 11 and Example 10 that the coating method using ultrasonic spray is conducive to further improving the consistency of the microporous layer, thereby improving the hydrophobicity of the microporous layer.
[0166] It can be seen from Table 4 that the introduction of cerium complexes has little effect on the vertical resistance and permeability of the gas diffusion layer. This is because the cerium complex has the best dispersibility in the slurry, is not easy to agglomerate and precipitate during the molding process, can be evenly dispersed in the conductive material and hydrophobic material with larger size, and will not block the pore structure formed by the conductive material and the hydrophobic material, so that the gas diffusion layer maintains good mass transfer capacity. At the same time, the good dispersibility of the cerium complex will not locally agglomerate to cause electronic insulation, thereby causing local short circuits in the gas diffusion layer and increasing the vertical internal resistance. While giving the gas diffusion layer the ability to quench free radicals, the cerium complex has little effect on the molding effect of the microporous layer, and has little effect on the mass transfer and electrochemical properties of the gas diffusion layer. In D4-D-GDL-4-1 prepared in Comparative Example 4, since the nano-scale cerium oxide particles are very easy to agglomerate during the molding process, and the compatibility of inorganic metal oxides and hydrophobic materials is poor, the poor compatibility and the cerium oxide particles formed by agglomeration will hinder the mass transfer of the gas diffusion layer, and will form a local current circuit to increase the internal resistance. Comparative Example 4 shows that the poor dispersibility of nano-cerium oxide and the easy agglomeration of nanomaterials will sharply reduce the mass transfer capacity and electrochemical properties of the gas diffusion layer when it is used as an additive to the gas diffusion layer.
[0167] The gas diffusion layers prepared in Examples 7-13 and Comparative Examples 1-4 were used to prepare membrane electrodes, and performance tests were conducted. The test results are shown in Table 5.
[0168] Table 5
[0169]
[0170] It can be seen from Table 5 that the embodiment of the present invention effectively improves the durability of the membrane electrode by introducing the cerium complex into the microporous layer. After running for 100 hours, the voltage loss does not exceed 0.02V, and the hydrogen permeation current is not higher than 2.9mA / cm 2@0.4V. In Comparative Examples 1-3, since no free radical quencher cerium complex was introduced, the voltage loss was as high as 0.04V after 100h of operation, and the hydrogen permeation current was as high as 3.2mA / cm 2 @0.4V or more, the durability of the membrane electrode is poor. In Comparative Example 4, the free radical quencher introduced is cerium oxide. Due to the high vertical resistance of the gas diffusion layer and the low mass transfer capacity, the initial voltage of the membrane electrode is low. Although the voltage decay is low after 100 hours of operation, the practicality of this low-output membrane electrode is not strong and its application is limited.
[0171] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0172] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A microporous layer, characterized in that: include: A hydrophobic material, a conductive material and a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce 3+ or Ce 4+ The ligand of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound.
2. The microporous layer according to claim 1, characterized in that The cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl-β-cyclodextrin or water-soluble polymers of these cyclodextrin compounds; Preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin or (2-hydroxypropyl)-β-cyclodextrin; More preferably, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin or γ-cyclodextrin.
3. The microporous layer according to claim 1, characterized in that The crown ether compounds include 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4, 1,7-diaza-12-crown-4, triaza-12-crown-4, benzo-15-crown-5, cyclohexane-18-crown-6, cyclohexane-15-crown-5, 24-crown-8, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, 1-aza-15-crown-5, dicyclohexane-18-crown-6, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, dicyclohexyl-18-crown-5, dicyclohexane-18-crown-6, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6, dicyclohexyl-18-crown-6, dicyclohexane ... Aza-18-crown-6, 4,10-diaza-15-crown-5-ether, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetra-15-crown-5-phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds; Preferably, the crown ether compound includes at least one of 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5, 4,13-diaza-21-crown-7, dicyclohexyl-18-crown-6, 18-crown-6, 15-crown-5, 21-crown-7, 24-crown-8 or tetra-15-crown-5-phthalocyanine; More preferably, the crown ether compound includes at least one of 1-aza-18-crown-6-ether, 1-aza-15-crown-5, diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, dicyclohexyl-18-crown-6 ether, 15-crown-5 or 18-crown-6.
4. The microporous layer according to claim 1, characterized in that The cerium complex comprises at least one of a complex formed by cerium and a cyclodextrin compound and a complex formed by cerium and a crown ether compound; Optionally, the complex formed by the cerium and the cyclodextrin compound includes at least one of a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (IV)-carboxymethyl-β-cyclodextrin complex, a cerium (IV)-methyl-β-cyclodextrin complex, a cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, a cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex or a cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex; Optionally, the complex formed by the cerium and crown ether compounds includes: cerium (III)-1-aza-18-crown-6-ether complex, cerium (III)-1-aza-15-crown-5 complex, cerium (III)-diaza-18-crown-6 complex, cerium (III)-diaza-15-crown-5 complex, cerium (III)-4,10-diaza-15-crown-5 complex, cerium (III)-4,13-diaza-21-crown-7 complex, cerium (III)-diaza-18-crown-6 complex, cerium (III)-diaza-15-crown-5 complex, cerium (III) ...8-crown-6 complex, cerium (III)-diaza-15-crown-5 complex, cerium (III)-diaza-21-crown-7 complex, cerium ( At least one of cyclohexyl-18-crown-6 ether complex, cerium (IV)-dicyclohexyl-18-crown-6 ether complex, cerium (III)-18-crown-6 complex, cerium (IV)-18-crown-6 complex, cerium (III)-15-crown-5 complex, cerium (III)-21-crown-7 complex, cerium (III)-24-crown-8 complex or cerium (IV)-tetra-15-crown-5-phthalocyanine complex; Preferably, the cerium complex comprises at least one of a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (III)-1-aza-18-crown-6-ether complex, a cerium (III)-1-aza-15-crown-5 complex, a cerium (III)-diaza-18-crown-6 complex, a cerium (III)-dicyclohexyl-18-crown-6 complex, a cerium (III)-18-crown-6 complex, and a cerium (III)-15-crown-5 complex; More preferably, the cerium complex includes at least one of: cerium (IV)-α-cyclodextrin complex, cerium (IV)-β-cyclodextrin complex, cerium (III)-1-aza-15-crown ether-5 complex, cerium (III)-dicyclohexyl-18-crown-6 ether complex, and cerium (III)-18-crown ether-6 complex.
5. The microporous layer according to any one of claims 1 to 4, characterized in that The mass ratio of the conductive material, the hydrophobic material and the free radical quencher is (10-200):(5-50):(0.1-10), preferably (10-100):(5-40):(0.1-5), and more preferably (10-60):(5-30):(0.1-1); And / or, the hydrophobic material includes at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, polychlorotrifluoroethylene, and ethylene-chlorotrifluoroethylene copolymer; preferably at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer; more preferably polytetrafluoroethylene. And / or, the conductive material includes at least one of solid carbon, porous carbon, solid graphite, expanded graphite, conductive carbon black, and carbon nanotubes.
6. A gas diffusion layer, characterized in that: The invention comprises a base layer and a microporous layer, wherein the microporous layer is the microporous layer according to any one of claims 1 to 5.
7. The gas diffusion layer according to claim 6, characterized in that: The base layer includes a carbon material layer and a hydrophobic material; Optionally, the carbon material layer includes at least one of carbon paper, carbon cloth, carbon felt, and carbon black paper; preferably, the carbon material layer includes carbon paper, and further preferably, the carbon paper has an average thickness of 80 to 400 μm, a porosity of 50 to 95%, and an average pore size of 10 to 100 μm; preferably, the carbon paper has an average thickness of 110 to 360 μm, a porosity of 60% to 90%, and an average pore size of 15 to 90 μm; more preferably, the carbon paper has an average thickness of 140 to 320 μm, a porosity of 70% to 85%, and an average pore size of 20 to 80 μm. Optionally, the hydrophobic material includes at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-propylene copolymer, ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene-ethylene copolymer, polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer, vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, polyvinyl fluoride, polychlorotrifluoroethylene, and ethylene-chlorotrifluoroethylene copolymer; preferably at least one of polytetrafluoroethylene, tetrafluoroethylene-hexafluoropropylene copolymer, ethylene-tetrafluoroethylene copolymer, polyvinylidene fluoride, polyvinyl fluoride, and tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer; more preferably polytetrafluoroethylene.
8. The gas diffusion layer according to claim 6, characterized in that: The average thickness of the microporous layer is 10-70 μm, and the average pore size is 0.05-2 μm. Preferably, the average thickness of the microporous layer is 15-60 μm, and the average pore size is 0.05-0.8 μm; more preferably, the average thickness of the microporous layer is 15-45 μm, and the average pore size is 0.08-0.5 μm; And / or, the average thickness of the base layer is 80-400 μm, the porosity is 50-95%, and the average pore size is 10-100 μm; preferably, the average thickness of the base layer is 110-360 μm, the porosity is 60%-90%, and the average pore size is 15-90 μm; more preferably, the average thickness of the base layer is 140-320 μm, the porosity is 70%-85%, and the average pore size is 20-80 μm.
9. The gas diffusion layer according to claim 6, characterized in that: The base layer further comprises a free radical quencher, wherein the free radical quencher comprises a cerium complex, and the central ion of the cerium complex comprises Ce. 3+ or Ce 4+ At least one of the ligands of the cerium complex comprises at least one of a cyclodextrin compound or a crown ether compound; Optionally, the cyclodextrin compound includes at least one of α-cyclodextrin, β-cyclodextrin, γ-cyclodextrin, methyl-β-cyclodextrin, butyl-γ-cyclodextrin, acetyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, succinyl-β-cyclodextrin, succinyl-α-cyclodextrin, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxyethyl)-β-cyclodextrin, (2-hydroxypropyl)-γ-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, triacetyl-β-cyclodextrin or water-soluble polymers of these cyclodextrin compounds; Optionally, the crown ether compound includes 18-crown-6, 15-crown-5, 12-crown-4, 1-aza-12-crown-4-ether, 1,7-diaza-12-crown-4, triaza-12-crown-4, benzo-15-crown-5, cyclohexane-18-crown-6, cyclohexane-15-crown-5, 24-crown-8-ether, dicyclohexane-24-crown-8, dicyclohexyl-18-crown-6 ether, 1-aza-15-crown-5 , diaza-18-crown-6, 4,10-diaza-15-crown-5-ether, 4,13-diaza-21-crown-7, 1-aza-18-crown-6-ether, dibenzo-30-crown-10, dibenzo-24-crown-8-ether, 21-crown-7, benzo-21-crown-7-ether, dibenzo-21-crown-7-ether, tetra-15-crown-5-phthalocyanine or at least one of the nitro, amino, hydroxyl, carboxyl or alkylated derivatives of these crown ether compounds; Preferably, the cerium complex includes a cerium (IV)-α-cyclodextrin complex, a cerium (IV)-β-cyclodextrin complex, a cerium (IV)-γ-cyclodextrin complex, a cerium (IV)-carboxymethyl-β-cyclodextrin complex, a cerium (IV)-methyl-β-cyclodextrin complex, a cerium (IV)-(2-hydroxyethyl)-β-cyclodextrin complex, a cerium (IV)-(2-hydroxypropyl)-γ-cyclodextrin complex or a cerium (IV)-(2-hydroxypropyl)-β-cyclodextrin complex, a cerium (III)-1-aza-18-crown-6-ether complex, a cerium (III)-1-aza-15-crown-5-ether complex, a cerium (III)-diaza-1 At least one of a cerium (III)-8-crown-6 complex, a cerium (III)-4,10-diaza-15-crown-5-ether complex, a cerium (III)-4,13-diaza-21-crown-7 complex, a cerium (III)-dicyclohexyl-18-crown-6 complex, a cerium (IV)-dicyclohexyl-18-crown-6 complex, a cerium (III)-18-crown-6 complex, a cerium (IV)-18-crown-6 complex, a cerium (III)-15-crown-5 complex, a cerium (III)-21-crown-7 complex, a cerium (III)-24-crown-8 complex or a cerium (IV)-tetra-15-crown-5-phthalocyanine complex; Optionally, in the base layer, the mass ratio of the carbon material layer, the hydrophobic material and the free radical quencher is 100:(1-50):(0-10), preferably 100:(3-30):(0-9), and more preferably 100:(5-25):(0-5).
10. A method for preparing a gas diffusion layer according to any one of claims 6 to 9, characterized in that: The method comprises the following steps: dispersing and mixing a hydrophobic material, a free radical quencher, a conductive material and a surfactant in a solvent to obtain a microporous layer slurry, coating the microporous layer slurry on a substrate layer, and obtaining a gas diffusion layer through drying and heat treatment.
11. The method for preparing a gas diffusion layer according to claim 10, characterized in that: The preparation method of the substrate layer comprises: impregnating the carbon material layer in a hydrophobic modified impregnation liquid, drying and heat treating to obtain the substrate layer, wherein the hydrophobic modified impregnation liquid comprises a hydrophobic material and a solvent; Optionally, the hydrophobically modified impregnation liquid further comprises at least one of a free radical quencher or a surfactant; preferably, in the hydrophobically modified impregnation liquid, the mass ratio of the solvent, the hydrophobic material, the free radical quencher and the surfactant is 100:(0.4-20):(0-4):(0-4), more preferably 100:(1-10):(0-3):(0-3), and even more preferably 100:(2-10):(0-2):(0-2); Optionally, the solvent includes water. Preferably, the solvent also includes a lower aliphatic alcohol, and the lower aliphatic alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol, and / or, in the solvent, the mass ratio of water to the lower aliphatic alcohol is 1:(0-4); Optionally, the immersion time is 1 to 30 minutes; Optionally, the drying method includes air drying or freeze drying. Preferably, the air drying temperature is 50 to 150° C., and the time is 3 to 60 minutes; the freeze drying temperature is -80° C. to 0° C., and the time is 4 to 48 hours; Optionally, the heat treatment temperature is 240-400° C., and the time is 1-10 min.
12. The method for preparing a gas diffusion layer according to claim 10, characterized in that: The solvent includes water, preferably, the solvent also includes a lower aliphatic alcohol, the lower aliphatic alcohol includes at least one of ethanol, isopropanol, n-propanol, n-butanol or tert-butanol; and / or, in the solvent, the mass ratio of water to the lower aliphatic alcohol is 1:(0-4); And / or, in the microporous layer slurry, the mass percentage of the surfactant is 0.1-15%, preferably 0.5-10%, more preferably 1-8%; And / or, the coating includes at least one of blade coating, slit coating, roller coating, extrusion coating, micro-concave transfer coating or spray coating, preferably blade coating, slit coating or spray coating; further preferably, the nozzle of the spray coating is selected from one of a pressure nozzle, a rotary nozzle, a two-phase flow nozzle, an ultrasonic nozzle or an electrostatic nozzle, more preferably an ultrasonic nozzle; And / or, the drying method includes at least one of air drying or freeze drying; preferably, the air drying temperature is 50-150°C, and the time is 3-60 minutes; the freeze drying temperature is -80°C-0°C, and the time is 4-48 hours; And / or, the heat treatment temperature is 250-400° C., and the time is 1-10 min.
13. A membrane electrode, characterized in that: The invention comprises a gas diffusion layer according to any one of claims 6 to 9 or a gas diffusion layer prepared by the method according to any one of claims 10 to 12.
14. The membrane electrode according to claim 13, characterized in that: The membrane electrode also includes a proton exchange membrane, an anode catalyst layer and a cathode catalyst layer. The anode catalyst layer and the cathode catalyst layer are respectively arranged on both sides of the proton exchange membrane. The gas diffusion layer is arranged on the side of the anode catalyst layer and the cathode catalyst layer away from the proton exchange membrane.
15. A fuel cell, characterized in that: Comprising the membrane electrode according to claim 13 or 14.
Citation Information
Patent Citations
Reduced degradation of ion-exchange membranes in electrochemical fuel cells
CN100468853C
Gas diffusion layer and preparation method and application thereof
CN117117209A